FAMEBASE VER. 2.0 – Hệ quản trị cơ sở dữ liệu cho người sử dụng đầu cuối - Vuong, L.T.; Binh, N.T.; Dung, V.A.; Hà, V.N.; Hung, T.D.; Thuong, H.V.; Quang, N.D. (Journal of Computer Science and Cybernetics, 2018)
FAMEBASE VER. 2.0 – Hệ quản trị cơ sở dữ liệu cho người sử dụng đầu cuối